If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+4)=-7(x+2/9)
We simplify the equation to the form, which is simple to understand
2(x+4)=-7(x+2/9)
Simplifying:
2*(x+4)=-7*(x + 0.222222222222)
Reorder the terms in parentheses
+(+2x+8)=-7*(x + 0.222222222222)
Remove unnecessary parentheses
+2x+8=-7+*(+x + 0.222222222222+)
Reorder the terms in parentheses
+2x+8=+(-7x-1.55555555556)
Remove unnecessary parentheses
+2x+8=-7x-1.55555555556
We move all terms containing x to the left and all other terms to the right.
+2x+7x=-1.55555555556-8
We simplify left and right side of the equation.
+9x=-9.55555555556
We divide both sides of the equation by 9 to get x.
x=-1.06172839506
| 12x^2+8x-7= | | b=1.5-2 | | t=(3t)(70m^2) | | 3(f+4)+2f= | | 4y+17.6=10(y-1) | | 4x-5(2x-3)=-15 | | 4a=6 | | 0=6x^2+12x+8 | | 7-5(-3-8n)=-46+6n | | -3-4x+20x^2= | | 8x-4=7x+4 | | 2(x+1)=x-7 | | [x+4]=17 | | M+2M+6M-4= | | 4(2m+5)=7a-3 | | b+11/3= | | 13-r=4-6m | | 72=16x | | 5x^2=250 | | 7x+x=4-x+3+4 | | 8+2.5=3n | | -5x-2=3+4x+5 | | 3-2n=2+3n | | 4x^2+10x+6=2x^2+6x+4 | | 6(2x+7)+3(x-10)= | | 16-2m=5m+8 | | 7-3[x+2]=4 | | 7x+x=4 | | x^3+5x^2+3x=0 | | 76=-3x+2(6x-16) | | 9+8(x+3)= | | 15+4[m-2]=21 |